Factors Affecting Rice Production and Land Usages in Banten Province, Indonesia - Siagian, Viktor - (Advances in Social Sciences Research Journal, 2020)
Banten Province has a harvested area of paddy fields on the 2017 year of 415,687 ha and production of 2,369,731 tons of unhusked rice. The objectives of this study are: 1) Knowing the priority of resources and agricultural inputs use for food production, 2) Knowing the factors that influence the productivity of rice in irrigated land in Banten Province, 3) Knowing the efficiency of the use of production inputs. The sampling method used purposive sampling with 90 respondents. The analytical method used the Analytical Hierarchy Process (AHP) and multiple linear regression of Cobb Douglas production functions. The results of the study are: 1) The priority strategy in increasing food production is to increase the use of irrigated rice fields, so that the goal is achieved by increasing the crop index, this can be done by prioritizing the optimization of agricultural machinery 2) Significant factors that affecting the production of paddy rice in the irrigated wetland paddy field in Rainy Season 2017/2018 are the use of urea fertilizer, the amount of use of solid organic fertilizer, the amount of use of human labor rent, and the arable land area, 3). The cumulative elasticity is 1.45, which is elastic, meaning that the addition of 1% of the production factor will increase production by 1.45% or increasing return to scale. So rice farming in irrigated land is relatively efficient. To increase production, it is necessary to increase rice productivity and crop index in irrigated paddy fields. Keywords: Factors production, efficiency, priority analysis, rice, land usage.